Analysis of Factors Influencing the Decision of Cooked Food Vendors on KNUST Campus to Practice Book Keeping - Nimoh, Fred; Tham-Agyekum, Enoch Kwame; Dankwah, Gabriel; Amoakwa, Kofi Takyi; Sakye, Edwin (Jurnal Social Economic of Agriculture, 2023)
Proper bookkeeping practices are essential for business performance and sustainability. Unfortunately, most small and medium-scale businesses, including food vending businesses, do not practice proper bookkeeping and, thus, suffer in making financing and investment decisions regarding their operations. Using cross-sectional data from a sample of 70 vendors randomly selected from a population of 200 cooked food vendors on the KNUST campus, the research investigated the factors influencing the vendor's decision to practice proper bookkeeping in their business operations. Descriptive and inferential statistics were used to analyze the data. About 76% of the food vendors were aware of bookkeeping practices and acknowledged the value of bookkeeping as a tool to monitor their financial performance and identify strategies to enhance profitability. Two-thirds of the vendors practiced bookkeeping, with 56% keeping financial records and a third keeping inventory records. Among the various factors examined, age, educational level, awareness, startup capital, profitability, access to credit, and experience were identified as the significant factors affecting the decision of a cooked food vendor to practice bookkeeping. The study recommends the need for food vendors to consider bookkeeping as a priority activity to enhance their financial accountability, business growth, and informed decisions about their operations, and thus the overall performance and sustainability of food vending businesses.